IMPLEMENTASI PEMBELAJARAN PJOK BERBASIS PERMAINAN TRADISIONAL DAN DAMPAKNYA TERHADAP MINAT BELAJAR SISWA SEKOLAH DASAR - Akhmad Azlan Khoirurrozikin; Imron Nugroho Saputro (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
Physical Education, Sports, and Health (PJOK) learning in elementary schools needs to be designed in an engaging and enjoyable way to increase students' interest in learning. Low student interest in PJOK learning remains a common problem, mainly when learning is carried out monotonously and lacks variety. This study aims to determine the impact of implementing traditional game-based PJOK learning on elementary school students' interest in learning. This study used a quantitative approach with a quasi-experimental method using a one-group pretest–posttest design. The research subjects were 75 students in grades III, IV, and V of Muhammadiyah 1 Kartasura Elementary School. The research instrument was a questionnaire on PJOK learning interest compiled based on indicators of student interest, attention, feelings of pleasure, and active involvement. Treatment was given through traditional game-based PJOK learning for six meetings. Data were analyzed using descriptive and inferential statistics with a paired sample t-test. The results showed an increase in the average score of students' interest in learning after the implementation of traditional game-based PJOK learning compared to before the treatment. This finding indicates that traditional game-based PJOK learning has a positive effect on elementary school students' interest in learning. Thus, conventional game-based learning can be used as an alternative, innovative, and tailored learning strategy for physical education and health (PJOK) that addresses the needs and characteristics of students.